GREENWASHING'S RELATIONSHIP WITH MARKET REPUTATION AND CONSUMER DISCOUNT - Correa, Caroline Miranda [UNESP]; Camargo Ferraz Machado, Joao Guilherme de [UNESP]; Braga Junior, Sergio Silva [UNESP] (Univ Nove Julho, 2018)
Objective: The objective of this study was to analyze the relationship between perceived characteristics of greenwashing and brand reputation and consumer mistrust Method: A quantitative exploratory research was carried out utilizing a survey with a sample of 170 consumers collected in the State of Sao Paulo. Data analysis was performed using structural equation modeling using SmartPLS 2.0 M3 software. Originality/Relevance: The originality of this study is to evaluate the perception of the consumer focused on the aspects of the influence of greenwashing (green makeup on a product) on the reputation of the brand and the distrust that this type of perception can bring to the product. Thus, the research contributes with an interdisciplinary study whose scale and similar studies can use methodology. Results: It has been shown that the characteristics of greenwashing when perceived by the consumer affect the consumer's distrust of green products and the brand's reputation. Since trust and brand interfere directly with the consumer's purchasing decision Theoretical/methodological contributions: The methodology of data analysis used reinforces how much the Modeling by Structural Equations can contribute to the development of the theory in questions related to consumer behavior. As for the theoretical advance, it was possible to observe that further studies are needed to evaluate the relationship between greenwashing and brand reputation. Social contributions/to management: The main contribution of this study was to prove that greenwashing, when perceived by the consumer in green products in the retail, there is an immediate and real reflection on the reputation of the brand and the distrust in the product and this, for a company recovering, it is very costly and time-consuming.
Keywords: Greenwashing; Product; Retail; Green Marketing; Brand Reputation